Upper respiratory tract diseases in athletes in different sports disciplines - Galazka-Franta, A.; Jura-Szoltys, E.; Smolka, W.; Gawlik, R. (Journal of Human Kinetics, 2016)
Upper respiratory tract diseases in athletes are a very common medical problem. Training conditions in different sports disciplines increase the risk of upper respiratory disease. Epidemiological evidence suggests that heavy acute or chronic exercise is related to an increased incidence of upper respiratory tract infections in athletes. Regular physical exercise at high intensity may lead to transient immunosuppression due to high prevalence of allergic diseases in athletes. Regardless of the cause they can exclude athletes from the training program and significantly impair their performance. In the present work, the most common upper respiratory tract diseases in athletes taking into account the disciplines in which they most often occur were presented. The focus was laid on symptoms, diagnostic methods and pharmacotherapy. Moreover, preventive procedures which can help reduce the occurrence of upper respiratory tract disease in athletes were presented. Management according to anti-doping rules, criteria for return to training and competition as an important issues of athlete`s health were discussed.